Spondylolysis in young tennis players - Ruiz-Cotorro, A.; Balius-Matas, R.; Estruch-Massana, A. E.; Vilaro Angulo, J. (British Journal of Sports Medicine, 2006)
The general aetiology, diagnosis, and treatment of spondylolysis, a bone defect in the pars interarticularis of the vertebra, are reviewed. A retrospective study of young tennis players diagnosed between 2000 and 2004 with spondylolysis with or without spondylolisthesis, assessed by radiography and planar bone scintigraphy, is described. If the radiographic results were negative, computed tomography was performed. Sixty six cases were evaluated: 53 L5 lesions, eight L4 lesions, two L3 lesions, and one bilateral lesion at the L2 level. Two more lesions at two levels were found (bilateral L5 and unilateral L4 and L3 on the right side). Classification, treatment, and outcome of the cases are reported. A combination of radiography, planar bone scintigraphy, and SPECT is useful for evaluating spondylolysis in tennis players and recommending treatment. Use of a brace did not appear to achieve significant results.